Improved particle size control for the dispersion polymerization of methyl methacrylate in supercritical carbon dioxide - McAllister, Thomas D.; Farrand, Louise D.; Howdle, Steven M. (Wiley, 2016)
Dispersion polymerization is a well-established method of producing polymer particles that are easily handled and processed. With careful choice of reaction conditions this technique can yield well defined, spherical particles for a wide range of applications. The use of supercritical carbon dioxide (scCO2) as a reaction medium offers a route to performing these syntheses without excessive use of volatile organic solvents and minimizes work-up and disposal steps. However a significant drawback has been the fact that up till now the control of particle size and morphology from CO2 have been limited. This study presents control of particle size and morphology over an unprecedented range for a single stabilizer in scCO2 by coordinating a few simple parameters to tailor the conditions toward different sizes. Further, this study introduces the novel approach in scCO2 of using delayed monomer addition which allows considerable reduction of the batch-to-batch variability as well as reduced agglomeration between particles.